Effect of hyperemesis gravidarum on maternal renal health: An investigation of the levels of neutrophil gelatinase-associated lipocalin in maternal serum - Çöl Madendağ, İlknur; Eraslan Şahin, Mefkure; Madendağ, Yusuf; Şahin, Erdem; Karakükçü, Çiğdem (Journal of Surgery and Medicine, 2019)
Aim: Hyperemesis gravidarum (HG) is a severe condition that occurs in 0.8–2.0% of pregnant women and can lead to kidney damage. Within minutes of ischemic perfusion injury, renal distal tubular cells release neutrophil gelatinase-associated lipocalin (NGAL). The aim of this study was to assess the levels of NGAL in maternal serum after HG onset and the association between HG severity, renal ischemia, and subsequent kidney damage. Methods: In this case-control study, the control group comprised healthy volunteers with similar demographic characteristics. The HG patients were divided into three groups according to disease severity based on the Pregnancy-Unique Quantification of Emesis scale as follows: Mild (≤6); moderate (7–12); and severe (≥13). Demographic parameters, biochemical parameters, and serum NGAL levels were compared among the groups. Results: Serum glucose, serum blood urea nitrogen, serum creatinine, serum phosphorus, aspartate aminotransferase, and alanine aminotransferase levels were similar among the groups. Serum sodium levels were significantly higher in the severe HG group than in all other HG groups. Urine osmolarity was significantly higher in the moderate and severe HG groups than in the control and mild HG groups. There were no differences in serum NGAL levels among the groups. Conclusion: Our results suggested that serum NGAL levels were not altered in patients complicated by HG.